Epidemiological characteristics and pathogens attributable to hand, foot, and mouth disease in Shanghai, 2008–2013 - Yifei Fu; Qiao Sun; Bo Liu; Hongmei Xu; Yuanping Wang; Weiping Zhu; Lifeng Pan; Linying Zhu (Journal of Infection in Developing Countries)
Introduction: Hand, foot, and mouth disease (HFMD) is a common childhood illness caused by enteroviruses. A passive surveillance system has been implemented in Shanghai Pudong since 2008 and etiology surveillance since 2009.We characterized the epidemiology and the etiology of HFMD in Pudong from 2008–2013. Methodology: Health care providers were required to report any clinically diagnosed HFMD to Pudong District Center for Disease Control and Prevention. For all severe cases and randomly selected mild HFMD cases, throat or rectal swabs or feces were collected for enterovirus detection by real time reverse transcription polymerase chain reaction. Results: A total of 50,149 cases were reported, with average 8,508 per year (range: 3,577–13,202) and average incidence of 167.5/100,000 persons (range: 81.4–254.1/100,000 persons). HFMD was more likely to occur in children under five years of age (85.6%), while severe cases were more likely to happen in children under three years of age (63.9%). Every year in May or June, HFMD peaked in the region; two peaks were observed from 2011 to 2013.The most common etiologic agents are EV71 and CA16.Different types of enterovirus circulate in different years. EV71 was the predominant pathogen in severe cases. The proportions of EV71 in severe cases was higher than in mild cases at the children’s medical center (p<0.001). Conclusions: HFMD remains an important public health issue in Shanghai. HFMD pathogen surveillance is required for more types of enteroviruses besides EV71 and CA16, which would give a better picture of the etiology of HFMD.